The Influence of Tax Socialization, Tax Knowledge, Tax Sanctions, and Education Level on the Compliance of Urban and Rural Land and Building Tax (PBB-P2) Taxpayers in Sidoarjo Regency - Dirapuspita, Vincensia Rena; Widajantie, Tituk Diah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the influence of tax socialization, tax knowledge, tax sanctions, and education level on the compliance of Urban and Rural Land and Building Tax (PBB-P2) taxpayers in Sidoarjo Regency. Although annual PBB-P2 revenue has consistently increased and even exceeded its targets, the number of paid Tax Object Numbers (NOP) remains relatively low, indicating ongoing challenges in achieving optimal taxpayer compliance. This research employs a quantitative approach through a survey method by distributing questionnaires to taxpayers in the region. The collected data were analyzed using SmartPLS 4.0 to test the effect of the independent variables on taxpayer compliance. The results reveal that tax socialization, tax knowledge, tax sanctions, and education level all have a positive influence on taxpayer compliance. The model's R-squared value of 0.769 indicates that 76.9% of the variation in compliance is explained by these variables. These findings emphasize the importance of educational and regulatory factors in enhancing tax compliance. Therefore, it is recommended that local governments strengthen tax education programs, implement fair and transparent sanctions, and improve community education to optimize PBB-P2 revenue collection